2011
DOI: 10.1007/s10900-011-9368-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating a Community Based Participatory Approach to Research with Disadvantaged Women in the Southern Suburbs of Beirut

Abstract: This manuscript presents the evaluation of a 3 year community-based participatory research (CBPR) approach involving the testing of a psychosocial intervention to improve reproductive and mental health of married women in a disadvantaged community in Beirut, Lebanon. The community-based participatory approach involved a community advisory committee (CAC), a local women committee (LWC), and university researchers. The evaluation of the CBPR approach followed qualitative assessment which included: analysis of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 6 publications
1
14
0
Order By: Relevance
“…Study participants reported high levels of satisfaction and attendance was good [20]. Attrition rates were low for the study context, and from the results of the analyses employing multiple imputations there was very little bias introduced through missing outcome data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Study participants reported high levels of satisfaction and attendance was good [20]. Attrition rates were low for the study context, and from the results of the analyses employing multiple imputations there was very little bias introduced through missing outcome data.…”
Section: Discussionmentioning
confidence: 99%
“…Hay el Sellom in the southern suburbs of Beirut, Lebanon, an informal settlement of approximately 150,000 mainly Lebanese Shiites, with low levels of basic health care services, education and physical infrastructure [20]. …”
Section: Methodsmentioning
confidence: 99%
“…Community stakeholders can provide relevant firsthand knowledge and insight that could help to identify critical public health concerns and to design and implement research projects examining evidence‐based interventions . This insight is hypothesized to increase the relevance and feasibility of the interventions for community care and is especially important to researchers interested in interventions for use in community settings, effectiveness studies, and studies of the dissemination and implementation of evidence‐based practices in usual care settings . For example, collaboration with community stakeholders can provide information about the context of a community or agency, thereby allowing researchers to tailor implementation, maximize feasibility, and increase the external validity of evidence‐based practices .…”
mentioning
confidence: 99%
“…Despite the utility of CAPs as a method to increase community engagement in the research process (Ahmed and Palermo 2010; Southerland et al 2013) and relevance of the research itself (Kobeissi et al 2011), to our knowledge, this study is the first to evaluate why community stakeholders decide to participate in CAPs.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these mutual benefits include identifying issues of importance to the community, public health improvements, policy and system changes, and jointly authored papers and presentations (Baker et al 1999; Benoit et al 2005; Mayo et al 2009; Minkler et al 2008). Community stakeholders provide unique knowledge (Yonas et al 2013) and, in turn, increase the relevance and feasibility of interventions and implementation efforts (Kobeissi et al 2011). Moreover, actively involving the community in research can improve the informed consent process, study design, and study implementation (Strauss et al 2001).…”
Section: Introductionmentioning
confidence: 99%